Discovering usage behaviors and engagement in an Educational Virtual World. (June 2015) - Cruz-Benito, Juan; Therón, Roberto; García-Peñalvo, Francisco J.; Pizarro Lucas, Emiliana
Highlights: Usage behaviors and engagement can be determined from user interactions. User engagement in Virtual Worlds may depend on the system or content. Users can perceive/use these systems as educational tools or for social interaction. Usage patterns can be identified to provide managers with deep knowledge regarding users. User behaviors and engagement can be used to improve learning in Virtual Worlds. Abstract: This paper explores data retrieved from an Educational Virtual World to identify and validate behavior and usage patterns and engagement indicators. This data exploration is intended not to validate pre-defined questions or specific goals (for example, a comparison between engagement and academic scores) but to discover usage trends and obtain insights about users' usage of the system and their knowledge of and proficiency with the available resources and features. The engagement indicators and knowledge obtained from the analysis of these indicators regarding the users of the system, their desires, and their competencies with virtual resources will facilitate decision-making and planning by managers of the Virtual World to improve system adoption and learning effectiveness, correct usage mistakes, perform actions to enhance user exploitation of available features, and provide information to users on system usage. This knowledge and the actions based on it are capital in an eLearning ecosystem such as an Educational Virtual World, where students are able to perform tasks in 3D at any time or location without supervision.